Synthesis of 6-oxopyrimidin-1(6H)-yl benzamide derivatives and evaluation of their antibacterial and cytotoxic activity. Issue 3 (1st February 2016) - Devarasetty, Kiran; Tharikoppula, Giri; Sridhar, Tailor; Eppakayala, Laxminarayana; Kyasani, Mahesh; Arumugam, Premkumar; Pusuluri, Srinivas
ABSTRACT: A series of novel 2-alkylamino and 2, 4-dialkyl amino 6-oxopyrimidin-1(6H)-yl) benzamide derivatives were prepared in good yields from a base-catalyzed ring opening of oxadiazolo[3, 2-a]pyrimidin-5-one and evaluated for their antibacterial and cytotoxicity. Most of the compounds exhibited antibacterial activity. In particular, compounds5b and5k exhibited considerable antibiotic activity against Klebsiella pneumonia and Bacillus cereus . In addition, compounds5g and5i also inhibited the growth of two human tumor cell lines (A549 and H460) at micromolar concentrations. GRAPHICAL ABSTRACT: